Matewan [videorecording (DVD)] - Sayles, John, 1950-; Cooper, Chris, 1951-; Jones, James Earl; McDonnell, Mary (The Criterion Collection, 2019)
A wrenching historical drama that recounts the true story of a West Virginia coal town where the local miners struggle to form a union rose to the pitch of all-out war in 1920. Written and directed by John Sayles, this film issues an impassioned cry for justice that still resounds today.